The search for a common livelihood space between rural and industrial areas - Andi Ali Said Akbar; Oktafiani C. Pratiwi; Indaru S. Nurprojo; Syah Firdaus (Masyarakat, Kebudayaan dan Politik, 2020)
Rural areas, according to Law Number 6 of 2014 concerning Villages, are placed as the economic power behind the villages themselves, especially concerning the agricultural sector. Ideally, the village focused on the development of the agricultural sector. However, there are 158 factories in Purbalingga Regency located in rural areas. While the protection of the rural areas and the spatial planning of industry is unclear, there are conflicts primarily related to the designation of rivers, irrigation canals, agricultural features, settlements, and water and air pollution. This research explains the study of industrial space and the related functional arrangements, especially in the agriculture-based rural and industrial areas of Purbalingga. This paper based on the research results, which were determined using qualitative methods and a case study approach. The data collected through observations, a document-based study, and interviews. The informant selection techniques used were purposive and snowball. Data validity was confirmed using an interactive analysis model. This study interviewed eleven informants who were from the Agricultural Office in addition to the Chief of the Urban Village, a Former Chief of the Village, a Former Chief of the Urban Village, a Chief from Village, Village Officers, Public Society Institution activists, and affected farmers. The results of the study are as follows 1) Purbalingga Government has an unclear vision concerning its long-term planning for industrial areas. The lack can see it of harmony present in the development of rural and industrial areas causing conflict between the actors involved, 2) the high investment from Purbalingga Government brings in a new problem, which is the neglecting of both the agricultural and environmental interests present. This research concludes, the government allowed for the development of rural areas that otherwise prioritized the development of the industrial sector. It is done without considering spatial planning, causing a sustained conflict between the actors.